Analysis of the Need for E-SWS Development Integrated Ethnoscience and PBL Models for Global Warming to Facilitate Students' Knowledge and Communication Skills - Hermanda, Richi Junia; Asrizal; Harman Amir; Suherman, Dea Stivani (TIME in Physics, 2025)
21st-century education demans learning that enchances knowledge and develops communication skills. This study aims to analyze the need for developing an integrated ethnoscience-based E-LKPD on global warming, using a Problem-Based Learning (PBL) model to facilitate students’ knowledge acquisition and communication skills. The preliminary study was conducted at SMAN 1 Enam Lingkung, involving two physics teachers and 32 tenth-grade students in Phase E. A descriptive statistical analysis method was employed, utilizing questionnaire data, written performance assessments, and documentation of Mid-Semester Assessment (MSA) scores. The results show that the learning process still relies on conventional media and has not yet incorporated ICT effectively. Students demonstrated low levels of knowledge (average 42.59%) and communication skills (average 41.29%). Furthermore, teachers have not optimally integrated the ethnoscience approach and the PBL model into their instruction. Based on these findings, an E-LKPD design was developed as an innovative solution to enhance the quality of 21st-century learning, particularly in delivering contextual and meaningful content on global warming.